The Analysis of Emojis and Identities In The Comments Section on Instagram @Ussfeed: From Semiotics to Cyberpragmatics - Muhamad Hilal; Ribut Wahyudi (UIN Salatiga, 2025)
This study aims to explore the role of emojis in expressing users' political identity in @ussfeed's Instagram comment section, focusing on the types of emojis used, their linguistic functions, and the representation of socio-political identity. Using a qualitative approach, this study integrates Berger's (2010) semiotic theory and Huddy's (2001) Social Identity theory and enriches its analysis with a cyberpragmatics perspective (Yus, 2011) to examine comments related to political issues in the January- April 2024 period. The results reveal that emojis play an important role in enriching textual meaning by adding visual and emotional dimensions, with icons as the most dominant emoji type that reflects various semiotic functions in conveying literal, contextual, and abstract meanings. From a cyberpragmatics perspective, emojis function as a means of digital identity construction where users strategically choose certain emojis to express political affiliation (ingroup) while differentiating themselves from other groups (outgroup). This research provides valuable new insights into how emojis have become an effective communication tool in the digital age while highlighting their role in identity formation in online public spaces and their impact on social interaction and self-representation in the digital world. At the end of this article, the author adds limitations of research and suggestions for future research.